PENYELIDIKAN DAN PENYIDIKAN MENGGUNAKAN TEKNIK INTEROGASI REKAMAN AUDIO VISUAL DALAM PEMBERKASAN PERKARA TINDAK PIDANA PADA POLRESTABES MEDAN - Damos Christian Aritonang, Syafrudin Kalo, M. Hamdan, Mahmud Mulyadi (Fakultas Hukum Universitas Komputer Indonesia, 2022)
The filing of cases begins with the Minutes of Examination (BAP). In making the Minutes of Investigation, both Witnesses and Suspects, for Investigators it is often difficult because the number of cases handled makes the Investigator not focus on revealing and making light of a criminal act. Not to mention, in the interrogations (also called